The distribution and host range of Batrachochytrium dendrobatidis in New Zealand, 1930–2010: Ecological Archives E094‐192. Issue 9 (1st September 2013) - Shaw, Stephanie D.; Skerratt, Lee F.; Haigh, Amanada; Bell, Ben D.; Daglish, Lisa; Bishop, Phillip J.; Summers, Rachel; Moreno, Virginia; Melzer, Sabine; Ohmer, Michel; Herbert, Sarah; Gleeson, Dianne; et al.
Abstract : Chytridiomycosis caused by the fungal invasive pathogen Batrachochytrium dendrobatidis (Bd) was first detected in 1999 in Christchurch, New Zealand, in the Australian introduced frog species Litoria raniformis . It was detected in wild native frogs in the critically endangered Leiopelma archeyi in 2001 on the Coromandel Peninsula and has been suggested as responsible for a mass decline (88%) in that population between 1994 and 2002. We report the current distribution, host species and prevalence, where known, of Bd in New Zealand, which is essential for conservation management of New Zealand native frogs ( Leiopelma spp.). The data set is structured so that it can be readily added to the Australian Bd database for further analyses. Our data included all regions in New Zealand and six offshore islands at 135 sites with 704 records from 23 contributors spanning collection dates 1930–2010. We report 54 positive sites from 132 positive individuals. We also detail negative findings, but declaring an area free from disease should consider the sensitivity of the test used and numbers of individuals tested. The data also included a comprehensive museum survey testing 152 individuals from five species (20 L. archeyi, 50 L. hochstetteri, 15 L. aurea, 40 L. ewingii, and 27 L. raniformis ) from 1930–1999 using histology and Bd‐specific immunohistochemistry. All museum specimens were negative, so the 1999 positive result is still the earliest record. In the L. archeyi Coromandel Ranges population, the period prevalence of Bd from 2006 to 2010 was relatively stable at 16%, but the number of animals tested remains low (up to N = 19) due to the now depleted population numbers. The period prevalence of Bd in the L. archeyi Whareorino population has remained both consistent and low (6%) between 2005 and 2010. In L. hochstetteri, L. hamiltoni, and L. pakeka all sampling for Bd has been negative. Positive Bd results have been found in all three Litoria spp., but Bd has not been found in the six offshore areas tested. Most data have been previously unpublished and represent the first confirmed reports of Bd in many regions and species in New Zealand.